Reconstruct History: Reconnaissance of Japanese Culture and the Orient by Kazuo Ishiguro in A Pale View of Hills - Meenakshi Rana (International Journal of Advanced Science and Technology, 2020)
The present discussion portrays the Japanese Culture as well as the Orient by A Pale View of Hills’ characters. A Pale View of Hills gives a medium to explore the attitudes between the East and the West. The present study gives details of Western culture’s impact on the culture of Japan. Kazuo Ishiguro represents how the characters are affected by the other culture with the help of their memories. The novel travels around after the World War II period by the main protagonist, Etsuko. The present research explains the situation of the characters that they feel they are displaced from their country. They live in an atmosphere of a western culture where values are changed. The main notion emphasizes on how Etsuko reconstruct history by making changes in their lives after the war. Furthermore, how reconnaissance of Japanese culture and the Orient is explained by the main character in the context of memories.